The urban thread - Bolon, Mila Alessandra (My University, 2010)
Johannesburg is changing. The council and other managing bodies are taking positive steps for the inclusion of a functioning public transport system. It is a system that is long overdue and one that which will have resonating effects for the city. This thesis will explore the changes that the new transport initiative may encourage. Focusing on the portion of road between the nodes of Rosebank and Illovo in Johannesburg’s northern suburbs, the study will analyse Oxford Road as an essential thread in the transportation system. Without the relevant design intervention the road runs the risk of becoming a pedestrian-unfriendly mobility route, akin to that of a highway, hostile and volatile in setting. The study aims to resist this by exploiting the effects of the public transport system, using them as a means of providing physical and visual form to the public realm and placing an emphasis on a comfortable and usable pedestrian environment